Factors that associated with TB patient admission rate and TB inpatient service cost: a cross-sectional study in China. Issue 1 (December 2016) - Hu, Hongyan; Chen, Jiaying; Sato, Kaori; Zhou, Yang; Jiang, Hui; Wu, Pingbo; Wang, Hong
Abstract Background China has recently adopted the "TB designated hospital model" to improve the quality of tuberculosis (TB) treatment and patient management. Considering that inpatient service often results in high patient financial burden, and therefore influences patient adherence to treatment, it is critical to better understand the TB patient admission rate and TB inpatient service cost, as well as their influential factors in this new model. Methods Quantitative and qualitative studies were conducted in two cities, Hanzhong in Shaanxi Province and Zhenjiang in Jiangsu Province, in China. Quantitative data were obtained from a sample survey of 533 TB patients and TB inpatient records from 2010–2012 in six county designated hospitals. Qualitative information was obtained through interviews with key stakeholders (40 key informant interviews, 14 focus group discussions) and reviews of health policy documents in study areas. Both univariate and multivariate statistical analyses were applied for the quantitative analysis, and the thematic framework approach was applied for the qualitative analysis. Results The TB patient admission rates in Zhenjiang and Hanzhong were 54.8 and 55.9 %, respectively. Qualitative analyses revealed that financial incentives, misunderstanding of infectious disease control and failure of health insurance regulations were the key factors associated with the admission rates and medical costs. Quantitative analyses found differences in hospitalization rate existed among patients with different health insurance and patients from different counties. Average medical costs for TB inpatients in Jurong and Zhenba were 7, 215 CNY and 4, 644 CNY, which was higher than the 5, 500 CNY and 3, 800 CNY limits set by the New Rural Cooperative Medical System. No differences in medical cost or length of stay were found between patients with and without comorbidities in county-level hospitals. Conclusions TB patient admission rates and inpatient service costs were relatively high. Studies of related factors indicated that a package of interventions, including health education programs, reform of health insurance regulations and improvement of TB treatment guidelines, are urgently required to ensure that TB patients receive appropriate care.